Crosstalk between mesenchymal stem cells and macrophages in inflammatory bowel disease and associated colorectal cancer - Mao, Fei; Kang, Jing-jing; Cai, Xiu; Ding, Ning-feng; Wu, Yun-bing; Yan, Yong-min; Qian, Hui; Zhang, Xu; Xu, Wen-rong (Contemporary Oncology/Współczesna Onkologia, 2017)
Mesenchymal stem cells (MSCs) are attractive seed cells for immunotherapy, tissue engineering and regenerative medicine due to their self-renewal and multidirectional differentiation abilities, diverse immunoregulatory functions and ease of isolation from a wide range of tissues. MSCs exert their immunoregulatory effect on immune cells via cell-to-cell contact and paracrine mechanisms. In turn, MSCs can also be modulated by immune cells. Macrophages are constantly present in the mucosa of the intestinal tract of mammals and play an important role in the development and progression of inflammatory bowel disease (IBD), a chronic and recurrent inflammatory disease of the gastrointestinal tract characterized by idiopathic mucosal inflammation. The increased morbidity and mortality of IBD have made it a disease hard to cure in the clinic. MSCs have emerged as an important tool for IBD therapy due to their abilities to differentiate into enterocyte-like cells and regulate inflammatory cells, especially macrophages. In this review, we discuss the recent advances in the interaction between MSCs and macrophages in diseases, with an emphasis on IBD. We propose that an optimized MSC-based therapy would provide a novel strategy for the treatment of IBD and the prevention of IBD-associated colorectal cancer (CRC).